Building Trust in The Digital Age: How HRM and Cybersecurity Collaborate for Effective Stakeholder Relations - Gagas Gayuh Aji; Suko Widodo; Ganjar Ndaru Aji; Gilang Gusti Aji; Dian Prawitasari (Management Analysis Journal, 2023)
This study emphasizes the crucial role of cybersecurity and public relations in the successful adoption of technology. To protect customer data and manage risks, organizations need robust cybersecurity measures. At the same time, building trust and differentiation through transparent communication and addressing customer concerns is vital. Recommendations include enhancing cybersecurity, training employees, prioritizing data privacy, maintaining ongoing public relations efforts, and collaborating with industry peers. By implementing these recommendations, organizations can navigate technology challenges, safeguard data, and cultivate a positive reputation.